THE EFFECT OF E-MARKETING STRATEGY ON THE PURCHASE DECISION OF PT. ROVCA CLOTHING PRODUCTS IN MAKASSAR - Jamaluddin.S (Jurnal Ekonomi, 2020)
This study aims to analyze the effect of E-Marketing strategy on product purchasing decisions of PT. Rovca Clothing in Makassar in 2017, in terms of the aspects of trust, ease (easy to use), information quality (information quality), and price (price). , as well as other research results that are relevant to the object under study, in this case primary data from the company PT. Rovca Clothing Makassar. The statistical analysis used in this study is multiple regression analysis using the SPSS 20 program. The results of this study indicate the variables of trust, ease of use, information quality, and price simultaneously (together) have a significant effect on product purchase decisions PT. Rovca Clothing Makassar in 2017. This is evidenced by the results of the F test with a significance level below 0.05. The variables of trust (trust), ease (easy to use), quality of information (information quality), and price (price) have a partial and significant effect on product purchasing decisions with each significance level below 0.05. The most dominant variable influencing product purchasing decisions is trust. This is evidenced by the Beta coefficient of trust is greater than the other variables, namely 0.233. Ease (easy to use), information quality (information quality), and price (price) have a partial and significant effect on product purchasing decisions with each significance level below 0.05. The most dominant variable influencing product purchasing decisions is trust. This is evidenced by the Beta coefficient of trust is greater than the other variables, namely 0.233. Ease (easy to use), information quality (information quality), and price (price) have a partial and significant effect on product purchasing decisions with each significance level below 0.05. The most dominant variable influencing product purchasing decisions is trust. This is evidenced by the Beta coefficient of trust is greater than the other variables, namely 0.233.